Предмет: Алгебра,
автор: master920
Помогите решить !!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
(√2)sin((п/3)-6x)=1
sin((п/3)-6x)=1/√2
(п/3)-6x=(-1)ⁿarcsin(1/√2)+kп=(-1)ⁿ(п/4)+kп
-6x=-(п/3)+(-1)ⁿ(п/4)+kп
x=[-(п/3)+(-1)ⁿ(п/4)+kп]/(-6)
x=(п/18)-(-1)ⁿ(п/24)-kп/6 , k∈Z
Автор ответа:
0
Ответ:
master920:
спасибо большое
Похожие вопросы
Предмет: Русский язык,
автор: ulyanakolod
Предмет: Русский язык,
автор: мишка79
Предмет: Русский язык,
автор: asy5
Предмет: Математика,
автор: Rezanova495